2014
DOI: 10.1080/13657305.2014.903309
|View full text |Cite
|
Sign up to set email alerts
|

Price Transmission in New Supply Chains—the Case of Salmon in France

Abstract: & In recent years there has been increased interest in the transaction forms in salmon markets, given that contracts have become more common, vertical mergers create firms that cover several levels in the supply chain, and futures markets have developed as a price risk tool. These are strong indications that salmon supply chains are developing in the same direction as supply chains for more processed food products. In this article we investigate to what extent this development has influenced the price transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 74 publications
3
23
0
Order By: Relevance
“…On the other hand, cross-commodity price transmission is mostly influenced by the substitutability and complementary relations among products. Recent studies on the horizontal price linkages in seafood markets include Nielsen (2004Nielsen ( , 2005; Asche et al (2005Asche et al ( , 2007Asche et al ( , 2012Asche et al ( , 2014; Nielsen et al (2007Nielsen et al ( , 2009 ;Vinuya (2007); Norman-Lopez and Asche (2008); Norman-Lopez (2009);and, Jimenez-Toribio et al (2010). Nielsen (2004) found that the "Law of One Price" is in force between the Norwegian and Danish herring markets.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, cross-commodity price transmission is mostly influenced by the substitutability and complementary relations among products. Recent studies on the horizontal price linkages in seafood markets include Nielsen (2004Nielsen ( , 2005; Asche et al (2005Asche et al ( , 2007Asche et al ( , 2012Asche et al ( , 2014; Nielsen et al (2007Nielsen et al ( , 2009 ;Vinuya (2007); Norman-Lopez and Asche (2008); Norman-Lopez (2009);and, Jimenez-Toribio et al (2010). Nielsen (2004) found that the "Law of One Price" is in force between the Norwegian and Danish herring markets.…”
Section: Introductionmentioning
confidence: 97%
“…They found a significant evidence of market integration, suggesting that the 'Law of One Price' holds for this industry. Asche et al (2014) examined market integration and price transmission for salmon in France, and found that price determination processes are different for fresh and smoke salmon.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the earlier work in price linkages between different levels in the value chains has been drawn from the agricultural economics literature (see, e.g., Brorsen et al, 1985;Gardner, 1975;Goodwin & Harper, 2000;Heien, 1980;Holloway, 1991;Kinnucan & Forker, 1987;Lyon & Thompson, 1993;Ward, 1982;Wohlgenant, 1985). Recently, a number of studies have examined price transmission for different fish species (see, e.g., Asche et al, 2007Asche et al, , 2014Floros, 2006;Guillotreau, 2004;Guillotreau et al, 2005;Jaffry, 2005;Jiménez-Toribio & García-del-Hoyo, 2006;Simioni et al, 2013). However, almost all of these studies have been conducted in developed countries focusing on commercial fish species.…”
Section: Introductionmentioning
confidence: 98%
“…This article investigates price transmission for two wild species (cod and Alaska Pollock) and one farmed species (salmon). Price transmission has been an important topic in this journal in recent years (Asche, Dahl, Valderrama, & Zhang, 2014;Pincinato & Asche, 2016;Singh, 2016), including a special issue on the topic (Fernández-Polanco & Llorente 2015; Gordon & Hussain, 2015;Gordon & Maurice, 2015;Singh, Dey, Laowapong, & Bastola, 2015;Tveteras, 2015). The current article takes on an insight from the hedonic price literature where Asche, Larsen, Smith, Sogn-Gruntvåg, and Young (2015) indicated that prices vary by retail chain.…”
mentioning
confidence: 99%